A novel fatigue life model considering surface-damage induced performance degradation. (1st April 2020) - Song, Jianan; Qi, Hongyu; Li, Shaolin; Shi, Duoqi; Yang, Xiaoguang
Highlights: A novel life prediction model was developed based on the CMD and fracture mechanics. Surface-damage-induced lifetime degradation was analyzed quantitatively. Effects of stress amplitude and exposure time on the surface-damage-induced degradation were investigated. The model was applied for materials with surface hot-corrosion, oxidation and vulcanization. Abstract: In this study, a novel life prediction model was proposed for the low-cycle fatigue life degradation induced by surface damage based on continuum damage mechanics and fracture mechanics. Compared to the traditional life prediction model, this model could predict the life of the affected surface areas and combine quantitative analysis and life analysis. Furthermore, the application of this model was also helpful to understand the strength degradation of specimens under different pre-exposure environments. The accuracy of this model was verified via a series of experimental data, including pre-exposure data in the hot-corrosion, static air, and wet H2 S environment. The results indicated that a longer pre-exposed time can reduce the fatigue strength of the surface material, thereby degrading the life of specimens.